2017
DOI: 10.1007/s12272-017-0947-5
|View full text |Cite
|
Sign up to set email alerts
|

Tryptanthrin prevents oxidative stress-mediated apoptosis through AMP-activated protein kinase-dependent p38 mitogen-activated protein kinase activation

Abstract: Tryptanthrin (6,12-dihydro-6,12-dioxoindolo-(2,1-b)-quinazoline) has been reported to have a variety of pharmacological activities. Present study investigated the cytoprotective effects of tryptanthrin on arachidonic acid (AA) + iron-mediated oxidative stress and the molecular mechanisms responsible. In HepG2 cells, pretreatment with tryptanthrin inhibited the cytotoxic effect of AA + iron in a concentration-dependent manner. In addition, tryptanthrin prevented the changes in the levels of apoptosis-related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Because we and others have reported several medicinal herbs and natural products that prevent oxidative stress via AMPK activation [ 4 , 7 10 ], we first monitored the effect of SDT (300 μ g/mL) on the temporal responses of AMPK and ACC (a representative downstream substrate of AMPK) phosphorylation. Based on immunoblot results, maximal increases in AMPK and ACC phosphorylation were observed at 0.5 h after SDT treatment, after which the levels gradually decreased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because we and others have reported several medicinal herbs and natural products that prevent oxidative stress via AMPK activation [ 4 , 7 10 ], we first monitored the effect of SDT (300 μ g/mL) on the temporal responses of AMPK and ACC (a representative downstream substrate of AMPK) phosphorylation. Based on immunoblot results, maximal increases in AMPK and ACC phosphorylation were observed at 0.5 h after SDT treatment, after which the levels gradually decreased.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that eupatilin, tryptanthrin, isorhamnetin, Paeonia obovata , and Buddleja officinalis protect cells from the effects of AA plus iron via AMPK activation [ 4 , 7 9 , 32 ]. AMPK is regarded as a master regulator of cellular homeostasis related to oxidative and metabolic stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptanthrin exhibited anti-neuroinflammatory action by inactivating NF-κB pathway to suppress TLR4-MyD88-mediated inflammation [38]. Additionally, tryptanthrin exerted a hepatoprotective effect on oxidative stress through the activation of AMP-activated protein kinase and p38 mitogenactivated protein kinase in HepG2 cells [39]. Therefore, such pharmacological activities improved the antiviral potential of tryptanthrin against HCoV-NL63 and other viruses.…”
Section: Discussionmentioning
confidence: 98%